Richard Pithouse, Writing the Decline: On the Struggle for South Africa’s Democracy (Historia, 2021)
Richard Pithouse’s Writing the Decline: On the Struggle for South Africa’s Democracy is a collection of essays detailing Pithouse’s responses to a variety of political events in South Africa and, to a lesser extent, globally in the period from 2008 to 2015. The essays are short comment pieces previously published in newspapers and online in outlets such as the Daily Maverick, Business Day and the South African Civil Society Information Service. As Pithouse puts it, Writing the Decline is not an academic work; instead it responds to events “as they happened” and has been “hammered out on the anvil of the present” (p 1). Many of the events Pithouse responds to will be familiar to readers, even if they are only casually engaged with South African and global political developments, while those acquainted with Pithouse’s academic work and activism will recognise many of the themes, foci and arguments he pursues in Writing the Decline.